2019
DOI: 10.3390/ijms20246115
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Derivative Exposure Promotes Functional Alterations of VSMCs and Consequent Atherosclerosis via ROS/p38/NF-κB-Mediated IL-6 Production

Abstract: Vanadium is a transition metal widely distributed in the Earth’s crust, and is a major contaminant in fossil fuels. Its pathological effect and regulation in atherosclerosis remain unclear. We found that intranasal administration of the vanadium derivative NaVO3 significantly increased plasma and urinary vanadium levels and induced arterial lipid accumulation and atherosclerotic lesions in apolipoprotein E-deficient knockout mice (ApoE−/−) murine aorta compared to those in vehicle-exposed mice. This was accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…OPG is an extracellular decoy receptor of RANKL and plays an important role in controlling RANK-mediated osteochondrogenic differentiation and calcification at the basal state [ 29 ]. By contrast, IL-6 drives SMC migration and promotes SMC chondrogenic differentiation and calcification [ 10 , 11 , 30 , 31 ]. Thus by upregulating IL-6 expression on one hand and suppressing OPG on the others TLR2 activation induces osteochondrogenesis and calcification.…”
Section: Discussionmentioning
confidence: 99%
“…OPG is an extracellular decoy receptor of RANKL and plays an important role in controlling RANK-mediated osteochondrogenic differentiation and calcification at the basal state [ 29 ]. By contrast, IL-6 drives SMC migration and promotes SMC chondrogenic differentiation and calcification [ 10 , 11 , 30 , 31 ]. Thus by upregulating IL-6 expression on one hand and suppressing OPG on the others TLR2 activation induces osteochondrogenesis and calcification.…”
Section: Discussionmentioning
confidence: 99%
“…It is accepted that an excessive burden of ROS may lead to abnormal cell growth, corresponding changes in intracellular homeostasis and damage to important components of in the cell when the antioxidant defense and/ or DNA repair mechanisms cannot balance the excess oxidants [29]. Oxidative stress, which results from the imbalance between the production and neutralization of ROS, is also reported to be involved in a large number of pathological states, such as Alzheimer's disease [30], Parkinson's disease [31], atherosclerosis [32], heart failure [33], myocardial infarction [34], and hepatic encephalopathy [35]. Importantly, oxidative damage caused by the production of ROS has been linked to the etiology of different types of human cancer [23,36].…”
Section: Ros Are the Main Molecules Involved In The Role And Mechanismentioning
confidence: 99%
“…[ 16,31 ] The activation of NF‐κB can also promote the production of IL‐6, and this process induces the differentiation, migration, and proliferation of VSMCs, leading to lipid accumulation and the formation of AS plaque. [ 32 ] In the present work, we demonstrated that the activation of NF‐κB was modulated by miR‐141‐5p inhibitors. Further experiments found that JSH‐23, an NF‐κB nuclear translocation inhibitor, played a similar role in VSMCs as miR‐141‐5p mimics.…”
Section: Discussionmentioning
confidence: 57%